Growth performance of Rambouillet sheep up to weaning age in an organized farm - KHAN, NUSRAT N; HAMADANI, AMBREEN; RATHER, MUBASHIR ALI; AHMAD, MIR SHABIR; BUKHARI, SYED SABA; AYAZ, AADIL; JALAL, HENNA; WANI, NAJIMAANA (The Indian Journal of Animal Sciences, 2021)
Data and pedigree information obtained from 4,186 birth records of Rambouillet Sheep collected from the Government Sheep Breeding and Research Farm, Reasi, Jammu and Kashmir were analyzed. The objective was to evaluate the performance and to estimate the genetic parameters of growth performance traits of Rambouillet Sheep. The mean of BW, WW, ADG, WW0.75, and KR were 2.86±0.04 kg, 13.85±0.26 kg, 122.11±2.94 gm/day, 7.18±0.09 kg and 17.01±0.11, respectively. The coefficient of variations (CV%) of all these traits under study were low ranging from 9.48 to 25.39% indicating that the traits had low variability. The effect of year and season was highly significant and non-significant, respectively on all the traits under study. Effect of sex was significant on BW, WW, ADG and WW0.75. 0.15 kg, 0.26 kg, 1.22 gm/day and 0.10 kg for BW, WW, ADG and WW0.75, respectively was observed in favour of male lambs. The effect of birth type was significant on BE and WW only. The heritability estimates were moderate for all traits and the genetic correlations ranged from -0.11±0.12 (between BW and WW) to 0.96±0.01 (between ADG and WW0.75). The overall breeding values for BW, WW, ADG, WW0.75, and KR were 2.80±0.04 kg, 13.86±0.23 kg, 122.89±2.58 kg/gm, 7.18±0.07 kg and 17.11±0.10, respectively. All correlations were significant whereas the trends were non-significant. The study indicated existence of genetic variability which can be harvested through selection.